2012
DOI: 10.47895/amp.v46i3.2041
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Early Laryngeal Cancer and Benign Vocal Cord Pathology among Patients Undergoing Videostroboscopy in Philippine General Hospital from 2008 to 2010

Abstract: ...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…8 Although the study population was different, these findings are also consistent with those of a local study by Carrillo et al showing that the most common chief complaint among patients who underwent videostroboscopy examination was hoarseness (77.6%), followed by globus sensation (5.9%), dysphonia (4.8%) and dysphagia (4.6%), while the most common pathology was vocal fold nodules (17.4%), followed by laryngoesophageal reflux (16.6%), vocal cord paralysis or paresis (12.9%), vocal cord cyst (10.4%), vocal cord polyps (8.1%) and presumptive cancer (6.1%). 14 12 Another study done by Souza et al reported an 18.9% prevalence of vocal cord pathologies. 15 A significant relationship was noted between smoking and laryngoscopic findings in this study.…”
Section: Discussionmentioning
confidence: 98%
“…8 Although the study population was different, these findings are also consistent with those of a local study by Carrillo et al showing that the most common chief complaint among patients who underwent videostroboscopy examination was hoarseness (77.6%), followed by globus sensation (5.9%), dysphonia (4.8%) and dysphagia (4.6%), while the most common pathology was vocal fold nodules (17.4%), followed by laryngoesophageal reflux (16.6%), vocal cord paralysis or paresis (12.9%), vocal cord cyst (10.4%), vocal cord polyps (8.1%) and presumptive cancer (6.1%). 14 12 Another study done by Souza et al reported an 18.9% prevalence of vocal cord pathologies. 15 A significant relationship was noted between smoking and laryngoscopic findings in this study.…”
Section: Discussionmentioning
confidence: 98%